A New Optimal Method of Tool Path Generation for Slow Tool Servo Turning of Complex Surface - Guo, Hangyan; Kang, Min; Zhou, Wei; Niu, Hengtai; Song, Bingwei (Manufacturing Technology Journal, 2020)
In order to improve the surface machining quality of slow tool servo (STS) turning in complex sur-faces, the optimal method of tool path generation (TPG) was studied. Taking into consideration the problem of large discrete errors and interpolation errors in TPG, equal height discretization method and interpolation algorithm for non-uniform nodes were proposd and the acceleration continuous condition was introduced. Simulation results showed that equal height discretization method could reduce the discrete error by more than 70%. The interpolation errors could be reduced to two orders of magnitude by transforming segment cubic Hermite interpolation into segment cubic spline inter-polation. Finally, the processing experiments were performed. The results showed that the form error PV value for the workpiece of the toric surface obtained by equal height discretization method and non-uniformity processing and segment cubic spline interpolation reached 0.002mm. The PV value of the sinusoidal array surface was about 0.009mm, and its surface roughness value was 0.064μm. The results proved this method can effectively reduce the discrete errors and interpolation errors, as well as improve the surface machining quality.
Keywords: Tool path; Equal height discretization; Hermite interpolation; Non-uniformity processing; Spline interpolation